Manajemen Mutu dalam Upaya Peningkatan Prestasi Sekolah - Indah Kusuma Pradini; Siti Rochanah; Amril Muhammad (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2016)
Research was conducted in SDN Tanah Tinggi 3 Tangerang and SD Islam Al-Ikhlas Tangerang. This research aims to knowing and analyzing how quality management is applied for improving school’s achievement. This study is focusing on quality management with the sub-focus of planning and actuating. The approach that used for this study is qualitative approach with comparative case study method descriptively. Based on the result and research data analysis, found that quality planning for improving school’s achievement are done by a work-meeting forum, each component in the school determines school’s objective based on existing vision and mission of the school and then the targeted objective will be decided by analyzing school’s needs. The analysis of school’s needs then will be used for arranging school’s programs and work programs for improving the achievement and planning for the future. The decision making was done then followed by the policies, from the planning for improving school’s achievement activities then a planning of improving school’s achievement could be created. In the practice, development of achievement improvement programs was done especially in the scope of Adiwiyata. it held by developing the policies of environmental caring and culture, developing the curriculum of environmental basis, developing participative basis activities and improving the management and structure and infrastructure empowerment. From those aspects, they can create improvement of school’s achievement on environmental aspect. For SDN Tanah Tinggi 3 on improving and developing its academic achievement needs curriculum development on student’s self-empower and extracurricular. Meanwhile for SD Islam Al-Ikhlas on human resources development needs more human resources.